Does financial inclusion gender gap persist in the digital world? - Sultana, Afroza (Asian Journal of Empirical Research, 2025)
This study examines whether digitalization effectively reduces the gender gap in financial inclusion across 37 low- and lower-middle-income countries between 2011 and 2021. Using Ordinary Least Squares (OLS) panel regression and a control function approach to check for endogeneity, the study explores the impact of digital variables, such as internet usage, digital payments, and a technology and innovation index, on the gender gap in account ownership, saving, and borrowing from formal financial institutions. Findings reveal that digitalization has a mixed impact. Internet usage significantly reduces the gender gap in saving, suggesting that increased connectivity can improve women’s ability to save. However, digital payments are associated with a wider saving gap, possibly reflecting unequal access or use among women. Digital variables were not statistically significant for account ownership and borrowing, indicating that structural barriers, such as socio-cultural norms, continue to limit women’s access to financial services. These results suggest that while digital infrastructure and access are essential, they are not sufficient on their own to achieve financial inclusion. The study emphasizes the necessity of comprehensive structural reforms, including the strengthening of women’s legal rights, the enhancement of financial regulations, the development of inclusive financial products tailored to women’s needs, the improvement of digital literacy, and the addressing of socio-cultural barriers, to ensure equitable and meaningful access to financial services for women.